APPLICATION OF FOREIGN LAW BEFORE THE EMIRATI JUDGE COMMENTARY ON THE RULING OF THE DUBAI COURT OF CASSATION IN APPEAL NO. 501 OF 2021 PERSONAL STATUS ISSUED JAN. 12, 2022 - Mohamed, Nashwa (Journal of Legal Sciences, 2023)
This research addresses the commentary on the appeal’s ruling of the Dubai Court of Cassation No. (501) Personal Status law of 2021 issued on 12 January, 2022, which is related to the application of foreign law before the Emirate judge. This ruling raised several legal principles and problems that require clarification and attention due to their importance. This is the first ruling on the application of the legislative amendment introduced by the UAE legislator to Article 1 (3) of the Personal Status Law No. (28) of 2005 by Federal Decree Law No. (29) of 2020. According to thereto, the application of foreign law before the Emirate judge is contingent on the adherence of one of the litigants by applying it in accordance with the attribution rule mentioned in Article 13 (1) of the amended Civil Transactions Act in 2020.